SWOT Analysis Approach: Tlogo Land Tourism Development Strategy in Malang Regency: Pendekatan Analisis SWOT: Strategi Pengembangan Wisata Tlogo Land Masa Kabupaten Malang - Dwikky Alfandi Irianto; Nasikh Nasikh (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
The diversity and attractiveness of tourism in Malang Regency can become a popular tourist destination for domestic and foreign tourists.Tlogo Land is one of the tourist attractions that are in great demand by tourists because of the charm of its natural beauty. However, during the Covid-19 pandemic, Tlogo Land faced various obstacles and challenges with the implementation of social restictions which caused a significant decrease in the number of visitors. This study aims to find out alternative development strategies and reveal the conditions of Tlogo Land tourism during the Covid-19 Pandemic.The method in this research is descriptive qualitative method, then analyzes internal and external factors of Tlogo Land Tourism through IFAS and EFAS matrix, SWOT diagrams and SWOT analysis tables. Based on the research that has been done, it can be seen that Tlogo Land Tourism during the Covid-19 Pandemic experienced a decrease in income and visitors, a reduction in the number of employees, and some of the facilties owned were damaged. The result of the SWOT analysis found nine alternative development strategies that can be used by Tlogo Land Tourism.